Length‐weight relationships of three Clupeiformes species from the Southeast coast of India, Bay of Bengal, Eastern Indian Ocean. (14th September 2020) - Karuppiah, Kannan; Ethiraj, Kannapiran; Paramasivam, Kodeeswaran; Rajendran, Kumar; Krishnamoorthy, Madhuri; Dharmaraj, Divya
Abstract: This study deals with the length‐weight relationships (LWRs) of three commercially important marine fishes belonging to the family Clupeidae from the major landing centers in Tuticorin, Mandapam, Thondi, Nagapattinam and Chennai in southeast coast of India. Monthly sampling were done at the respected landing centers from June, 2018 to April, 2019 from the commercial trawlers (with cod‐end mesh size of 25–35 mm) and gill netters (with different mesh size vary from 20 to 170 mm). The estimated ' b ' values ranged from 3.1215 ( Sardinella albella ) to 3.1819 ( Amblygaster clupeoides ) and ' a ' values varied from 0.0059 ( A. clupeoides ) to 0.0074 ( S. albella ). The study also provides a new maximum total length (TLmax ) for two species A. clupeoides and Sardinella fimbriata .